Human fallopian tube proteome shows high coverage of mesenchymal stem cells associated proteins. Issue 1 (19th February 2016) - Wang, Chenyuan; Liu, Yang; Chang, Cheng; Wu, Songfeng; Gao, Jie; Zhang, Yang; Chen, Yingjie; Zhong, Fan; Deng, Gaopi
Abstract : We report the largest scale MS based proteome of human fallopian tube (hFT). Ribosome, cytoskeleton, and vesicle associated proteins showed high abundance in hFT. Extraordinary high coverage of MSCs associated proteins in the hFT proteome. Abstract : The object of this research was to report a draft proteome of human fallopian tube (hFT) comprises 5416 identified proteins, which could be considered as a physiological reference to complement Human Proteome Draft. The proteomic raw data and metadata were stored in an integrated proteome resources centre iProX (IPX00034300). This hFT proteome contains many hFT markers newly identified by mass spectrum. This hFT proteome comprises 660 high-, 3605 medium- and 1181 low-abundant proteins. Ribosome, cytoskeleton, vesicle and protein folding associated proteins showed obvious tendency to be higher abundance in hFT. The extraordinary high coverage of mesenchymal stem cells (MSCs)-associated proteins were identified in this hFT proteome, which highly supported that hFT should contain a plenty of MSCs.